Resting-state functional brain connectivity in female adolescents with first-onset anorexia nervosa - Katrien F.M. Bracké; Laura Monteiro Rente Dias; Marisha N. Meijer; Cathelijne P.M. Steegers; Laurinde F. den Heijer; Tess van der Harst; Marjolein H.G. Dremmen; Meike W. Vernooij; Gwen C. Dieleman; Tonya White (NeuroImage: Clinical)
Objective: Women with anorexia nervosa (AN) have been shown to demonstrate differences in functional connectivity in brain regions associated with cognitive control, somatosensory processing, and emotion regulation. However, previous studies have been conducted on small samples and have inconsistent findings. Therefore, this study aimed to identify aberrant brain networks related to the core clinical symptoms of AN and to explore the longitudinal association with clinical outcome in a large population of adolescents experiencing their first episode of AN. Methods: Functional MRI (fMRI) of brain resting-state functional connectivity (RS-FC) of female adolescents with first-onset AN (n = 56) were compared to age- and education-matched typically developing (TD) adolescents (n = 64). To account for the severity of underweight, separate analyses were performed to investigate differences in RS-FC between underweight AN participants and TD adolescents, as well as between underweight (n = 30) and weight-restored AN (n = 26) participants. Clinical outcomes, i.e. body mass index and eating disorder (ED) symptoms, were assessed at baseline and one-year follow-up. Independent component analyses (ICA) were used to extract the brain networks of interest: the default mode (DMN), left and right frontoparietal (FPN), and the insular (IN) networks. Linear regression analyses were conducted to assess differences in RS-FC between AN and TD participants, as well as to assess whether RS-FC was associated with clinical symptoms at baseline and at one-year of follow-up. Two statistical models were used: model 1 adjusted for age and socioeconomic status (SES), and model 2 additionally adjusted for baseline anxiety and depressive symptoms. Results: Underweight AN participants had lower RS-FC between the DMN-IN, as well as between the FPN-IN compared to the TD adolescents. After correction for multiple testing, no significant differences in RS-FC were found between underweight AN participants and weight-restored AN participants, as well as between the whole AN group and the TD group. RS-FC was not associated with the severity of clinical symptoms at baseline nor at one-year of follow-up. Conclusion: AN is associated with changes in RS-FC between the FPN-IN and DMN-IN during the underweight state. These changes in RS-FC were no longer observed in weight-restored AN participants, emphasizing the impact of underweight on RS-FC in AN. Changes in these brain networks may partly explain the impaired cognitive control and difficulties with emotion and behavioral regulation in individuals with AN during the underweight state.